2020
DOI: 10.2147/idr.s235975
|View full text |Cite
|
Sign up to set email alerts
|

<p>Carbapenem-Resistant <em>Klebsiella aerogenes</em> Clinical Isolates from a Teaching Hospital in Southwestern China: Detailed Molecular Epidemiology, Resistance Determinants, Risk Factors and Clinical Outcomes</p>

Abstract: Little is known about the epidemiology and carbapenem-resistance determinants of carbapenem-resistant K. aerogenes (CRKA) isolated from a single medical center. The present study was initiated to characterize the molecular epidemiology and the carbapenemresistance mechanisms of CRKA isolated during 2012-2018 from a teaching hospital in southwest China, and to investigate the risk factors and clinical outcomes of CRKA infections as well. Methods: Pulsed-field gel electrophoresis (PFGE) was employed for epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Out of the 10 isolates, we discovered that two only contained the bla KPC-2 gene and three only contained the bla NDM-1 gene while, interestingly, five strains carried both the bla KPC-2 and bla NDM-1 genes. Previous studies have reported the presence of bla KPC or bla NDM genes in clinical K. aerogenes isolates from various countries ( Pulcrano et al, 2016 ; Franolić et al, 2019 ; Ma et al, 2020 ), including Brazil ( Bispo Beltrão et al, 2020 ; Soares et al, 2021 ). However, our literature review indicated that there has been only one study of K. aerogenes co-harboring both bla KPC and bla NDM genes, which was observed in China ( Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 10 isolates, we discovered that two only contained the bla KPC-2 gene and three only contained the bla NDM-1 gene while, interestingly, five strains carried both the bla KPC-2 and bla NDM-1 genes. Previous studies have reported the presence of bla KPC or bla NDM genes in clinical K. aerogenes isolates from various countries ( Pulcrano et al, 2016 ; Franolić et al, 2019 ; Ma et al, 2020 ), including Brazil ( Bispo Beltrão et al, 2020 ; Soares et al, 2021 ). However, our literature review indicated that there has been only one study of K. aerogenes co-harboring both bla KPC and bla NDM genes, which was observed in China ( Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ESBLs in K. aerogenes strains has been well-documented, leading to the use of carbapenems as a last-resort treatment for serious infections caused by these pathogens. However, previous studies have shown a high prevalence of antibiotic resistance to cephalosporins and carbapenems in clinically relevant K. aerogenes strains worldwide ( Ma et al, 2020 ). These infections pose a significant public health challenge due to the limited treatment options available and their elevated mortality rates ( Mulani et al, 2019 ; Denissen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…K. aerogenes isolates that harbor an extended range of beta-lactamase and carbapenemase genes and such strains are frequently associated with hospital outbreaks [15]. Recent research suggests that carbapenem resistance in K. aerogenes is mostly caused by overexpression of ESBLs and ampC enzymes harbored by efflux pumps and efflux pump inhibitors (EPIs) [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely associated with bloodstream, skin and soft tissue, respiratory, and urinary tract infections [16]. Recently, the emergence of carbapenem-resistant K. aerogenes and colistin-resistant K. aerogenes isolates in China is of concern [17][18][19][20]. However, the genetic background of K. aerogenes isolates recovered from clinical settings in China remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%